1993
DOI: 10.1002/bjs.1800800519
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized study of one- or two-layer anastomosis following oesophageal resection and cervical oesophagogastrostomy

Abstract: In a prospective randomized study, one- and two-layer anastomoses were compared following subtotal oesophagectomy and gastric substitution with cervical oesophagogastric anastomosis. After 54 one- and 53 two-layer procedures the rates of anastomotic leakage were the same (19 per cent). After a mean follow-up of 44 weeks, 13 of 51 patients (25 per cent) undergoing one-layer anastomosis and 28 of 50 (56 per cent) having the two-layer procedure complained of cervical dysphagia and required dilatation. The anastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
4

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 10 publications
2
43
0
4
Order By: Relevance
“…In our study, more than half of the radiological leaks were asymptomatic. Several authors have reported similar observations [10][11][12] .…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In our study, more than half of the radiological leaks were asymptomatic. Several authors have reported similar observations [10][11][12] .…”
Section: Discussionsupporting
confidence: 68%
“…The patients were kept non per os until a second GS study, and then were allowed oral feeding even if the second GS still showed a contained leak and remained asymptomatic. Zieren et al [10] , Tilanus et al [11] and Lee et al [12] , in their series, also observed that radiological leaks remained asympto matic.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Zieren and co-workers 210 Leak defined as any radiographically demonstrable extravasation of water-soluble medium at the site of anastomosis on day 7 postoperatively.…”
Section: Obertop and Bosschamentioning
confidence: 99%
“…mentioned techniques, most recent and even randomized trials have shown that there is really no big difference [1,2,14,15].…”
Section: Drainagc O F Cervical Esophagogastrostomymentioning
confidence: 99%